TERIPARATIDE [HUMAN PARATHYROID HORMONE (PTH) 1-34] FOR THE MANAGEMENT OF POST-THYROIDECTOMY HYPOCALCEMIA EXACERBATED BY CHYLE LEAK - Chiew, Ken Seng; Lim, Quan Hziung; Hee, Nicholas Ken Yoong; Paramasivam, Sharmila; Lim, Lee Ling; Ratnasingam, Jeyakantha; Vethakkan, Shireene (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Hypocalcaemia secondary to hypoparathyroidism is a common complication of thyroidectomy. Another less common but serious complication is chyle leak which may also lead to electrolyte abnormalities, including hypocalcaemia. We report a case of refractory hypocalcaemia following thyroidectomy complicated by chyle leak which was successfully managed with teriparatide. CASE A 37-year-old male had undergone total thyroidectomy with central and left lateral neck dissection for papillary thyroid carcinoma. After the surgery, up to 200 cc/day of milky fluid were noted in his neck drain. Biochemical analysis showed high triglyceride content (2.3 mmol/L), consistent with chyle. He was initially treated conservatively with total parenteral nutrition, pressure dressing and subcutaneous octreotide. On postoperative day (POD) 3, he had symptomatic hypocalcaemia (corrected calcium 1.95 mmol/L). PTH was undetectable (<0.5 pmol/L). However, despite intravenous calcium gluconate infusion, high doses of activated vitamin D and calcium supplements (calcitriol 4.5 mcg/day, alphacalcidol 2 mcg/day and calcium carbonate 6 g/day), his calcium level remained as low as 1.9 mmol/L by POD 10. Subcutaneous teriparatide was then started, titrated up to 20 mcg, bid. This stabilized his corrected calcium at 2.1 mmol/L. On POD 16, the chyle leak was successfully sealed surgically. By POD 19, his calcium level improved to 2.34 mol/L. Subcutaneous teriparatide was discontinued after a course of 14 days. To date, 5 months after his surgery, he is normocalcaemic while on alphacalcidol 2.5 mcg/day and calcium carbonate 3 g/day. His PTH remains undetectable. Chyle leak occurs in 0.5-1.4% of thyroidectomies and 2-8% of neck dissections. As the thoracic duct ends at the junction of the left subclavian and jugular veins, most chyle leaks occur following left neck dissection. About 70% of chyle consist of dietary fats. Hence, asides from calcium, chyle leak also results in loss of dietary fat-soluble vitamins, including vitamin D. CONCLUSION Post-thyroidectomy hypocalcaemia due to hypoparathyroidism can be exacerbated by chyle leak, thus necessitating use of parenteral therapy with teriparatide.